Lifelong learning reimagining age-specific classrooms by designing a socio-generative and intergenerational learning center based on sikolohiyang Pilipino - Sobremesana, Mariah Issabelle B.
As the Philippines gradually progressed towards becoming an "aging society," the proliferation of socially age-segregated institutions, such as the academe, further perpetuated ageist stereotypes and discrimination among older individuals. Although families were the most basic age-integrated institution where knowledge exchange was organic, there was an apparent decline in familial multigenerational interconnection due to more people relocating to find jobs to sustain themselves financially. It was, therefore, worth considering that learning could also thrive in non-familial multiage relationships. Fortunately, an emerging educational approach called intergenerational learning supported different generations to learn together and from each other while supervised by a trained educator. Since the practice originally stemmed from Western ideologies, the comprehensive design project sought to decentralize and indigenize through utilizing principles introduced from Sikolohiyang Pilipino (SP) and applying them in formal settings such as the classroom. It also aimed to suggest an alternative classroom design by integrating universal architectural design interventions to cater to the distinct capacities of generations. Providing a shared learning platform in Fairview, Quezon City encouraged intentional and spontaneous interactions between the young and old and generated positive social outcomes extending from the learners, workforce, and community.